SIMPELMAS: An Integrated Information System for Research and Community Service Using a Prototype Development Approach - Muzid, Syafiul; Murti, Alif Catur; Triyanto, Wiwit Agus (ISB Atma Luhur, 2025)
The Institute for Research and Community Service (LPPM) plays a strategic role in coordinating academic research and community engagement activities. However, fragmented data management continues to hinder performance evaluations and strategic decision-making in many universities. This study aims to develop SIMPELMAS (Research and Community Service Management Information System), an integrated platform designed to streamline the management of human resources, research, and community service data. Using a prototype-based development methodology, SIMPELMAS was implemented and tested in Universitas Muria Kudus. The system achieved high success rates in various aspects: over 95% in functionality, 99–100% in security, and 80–85% in user satisfaction. Key features such as proposal submission, fund monitoring, and final reporting functioned optimally. Integration testing confirmed effective data synchronization, while user feedback highlighted the need for improvements in user experience, particularly for students and new users. This study contributes to the digital transformation of higher education by providing a replicable model for academic information systems that support real-time monitoring, transparency, and data-driven governance. While the system has met key eligibility standards, further enhancements in user interface and mobile responsiveness are recommended to ensure broader usability and adoption.